A novel hybrid aspirin-NO-releasing compound inhibits TNFalpha release from LPS-activated human monocytes and macrophages - Fox Sarah; Gasco Alberto; Fruttero Roberta; Cena Clara; Lazzarato Loretta; Sheldrake Tara A; Marcarino Paolo; Turnbull Catriona M; Megson Ian L; Rossi Adriano G (BMC, 2008)
Abstract Background The cytoprotective nature of nitric oxide (NO) led to development of NO-aspirins in the hope of overcoming the gastric side-effects of aspirin. However, the NO moiety gives these hybrids potential for actions further to their aspirin-mediated anti-platelet and anti-inflammatory effects. Having previously shown that novel NO-aspirin hybrids containing a furoxan NO-releasing group have potent anti-platelet effects, here we investigate their anti-inflammatory properties. Here we examine their effects upon TNFα release from lipopolysaccharide (LPS)-stimulated human monocytes and monocyte-derived macrophages and investigate a potential mechanism of action through effects on LPS-stimulated nuclear factor-kappa B (NF-κB) activation. Methods Peripheral venous blood was drawn from the antecubital fossa of human volunteers. Mononuclear cells were isolated and cultured. The resultant differentiated macrophages were treated with pharmacologically relevant concentrations of either a furoxan-aspirin (B8, B7; 10 μM), their respective furazan NO-free counterparts (B16, B15; 10 μM), aspirin (10 μM), existing nitroaspirin (NCX4016; 10 μM), an NO donor (DEA/NO; 10 μM) or dexamethasone (1 μM), in the presence and absence of LPS (10 ng/ml; 4 h). Parallel experiments were conducted on undifferentiated fresh monocytes. Supernatants were assessed by specific ELISA for TNFα release and by lactate dehydrogenase (LDH) assay for cell necrosis. To assess NF-κB activation, the effects of the compounds on the loss of cytoplasmic inhibitor of NF-κB, IκBα (assessed by western blotting) and nuclear localisation (assessed by immunofluorescence) of the p65 subunit of NF-κB were determined. Results B8 significantly reduced TNFα release from LPS-treated macrophages to 36 ± 10% of the LPS control. B8 and B16 significantly inhibited monocyte TNFα release to 28 ± 5, and 49 ± 9% of control, respectively. The B8 effect was equivalent in magnitude to that of dexamethasone, but was not shared by 10 μM DEA/NO, B7, the furazans, aspirin or NCX4016. LDH assessment revealed none of the treatments caused significant cell lysis. LPS stimulated loss of cytoplasmic IκBα and nuclear translocation of the p65 NF-κB subunit was inhibited by the active NO-furoxans. Conclusion Here we show that furoxan-aspirin, B8, significantly reduces TNFα release from both monocytes and macrophages and suggest that inhibition of NF-κB activation is a likely mechanism for the effect. This anti-inflammatory action highlights a further therapeutic potential of drugs of this class.